English Occupational Needs of Garment and Apparel Fashion Technology Trainees of Ethiopian Federal Technical and Vocational Training Institute - SHEWANGIZAW, Gashaw (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This paper was aimed at investigating the English needs of garment and apparel fashion technology trainees of the Ethiopian Federal Technical and Vocational Training Institute. A sequential mixed research design was used to conduct this study. The data-gathering instruments were questionnaires, semi-structured interviews, and direct observation. All the trainees were considered to fill out the survey questionnaire. Besides, interviews were held with ten possessively selected trainees. The third data collection tool was direct observation. Three different observations were held in two different contexts. The interview and observation were used to clarify issues that had been discussed from the data collected through the questionnaire. The findings revealed that the most important English language skills for trainees’ future job are speaking, writing, listening, and reading in decreasing order of importance. About the ability of the trainees, they are relatively better in reading and listening than in speaking and writing skills. The important and difficult English language sub-skills for the trainees are also identified and prioritized concerning the English macro-skills. Finally, the preferred learning style of trainees is the visual learning strategy.